Collective Violence and Social Disintegration: A Study of Mass Violence as a Trigger off Crime and The Loss of Social Values in Society - Utari, Indah Sri (The Indonesian Journal of International Clinical Legal Education, 2019)
This study delves into the intricate interplay between collective violence and social disintegration, examining the repercussions of mass violence as a trigger for heightened criminal activities and the erosion of societal values. Through a comprehensive analysis of historical and contemporary instances of collective violence, the research aims to unravel the complex mechanisms that link such events to an increase in criminal behavior and the gradual breakdown of fundamental social norms. The investigation explores psychological, sociological, and economic dimensions to illuminate the multifaceted impact of collective violence on the fabric of society. The study endeavors to uncover how these violent events contribute to a loss of trust, exacerbate socio-economic disparities, and foster an environment conducive to criminality. By understanding these dynamics, the research seeks to provide valuable insights for policymakers, law enforcement, and community leaders. These insights can inform the development of effective strategies to mitigate the impact of mass violence on crime rates and work towards the preservation of foundational values that underpin social cohesion.